Stature Estimation from Clavicular Length Using Multidetector Computed Tomography in an Adult North Indian Population - Beniwal, Sonia; Aneja , Prachi Saffar; Saha, Susmita; Kapur, Neeru; Narula, Arjun (International Journal of Medical Toxicology and Forensic Medicine, 2026)
Background: Stature estimation is an essential component of the biological profile in forensic anthropology. When primary long bones are fragmented or unavailable, alternative skeletal elements must be evaluated. This study aimed to examine the relationship between adult Haryanvi clavicular measurements and stature using multidetector computed tomography (MDCT) and to evaluate the performance of population-specific regression equations. Methods: MDCT scans of 68 adult individuals (33 males, 35 females; aged 20–80 years) were evaluated, yielding 136 clavicular observations. Clavicle length was measured on 3D reconstructed images. Sex-specific differences, bilateral symmetry, and correlations with stature were statistically analyzed. Results: The left clavicle was significantly longer than the right side in both males (p = 0.0176) and females (p = 0.0247), though the absolute differences were small (~2 mm). The clavicular height index demonstrated significant sexual dimorphism when both sides were combined (p = 0.0083). Stature correlated moderately with clavicle length in the pooled sample (r = 0.5356, p < 0.0001) and weakly to moderately in females (r = 0.3625, p = 0.0020). Correlations in males were negligible and statistically non-significant (r = 0.1079, p = 0.3884). Conclusion: Clavicular length demonstrates modest predictive value for stature estimation in the pooled Haryanvi sample and female subgroup, but lacks predictive utility in males. Due to its limited accuracy, it should be utilized as an exploratory or secondary method when primary long bones are missing.